ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KONSUMEN DALAM PEMBELIAN SMARTPHONE XIAOMI (STUDI KASUS PADA MAHASISWA PENGGUNA SMARTPHONE XIAOMI DI UNIVERSITAS NUSA CENDANA) - Astin Naomi Saekoko; Antonio E.L. Nyoko; Ronald P C Fanggidae (Journal of Management Small and Medium Enterprises (SMEs), 2020)
This study aims to determine the factors that influence consumer behavior in purchasing Xiaomismartphones. The sample in this study amounted 100 respondents taken using a purposivesampling technique. This study uses a qualitative approach, which takes the object of research at theUniversity of Nusa Cendana. Data collection is done by the method of observation, interviews andquestionnaires. The results found that Psychology and Personal variables were the most influencevariables for consumers in purchasing Xiaomi smartphones. While the indicator "Has GoodQuality" is the biggest reason consumers decide to buy a Xiaomi smartphone. Keywords: Culture, Social, Personal, Psychology